A Three-Dimensional Electrospun Li6.4La3Zr1.4Ta0.6O12–Poly (Vinylidene Fluoride-Hexafluoropropylene) Gel Polymer Electrolyte for Rechargeable Solid-State Lithium Ion Batteries - Wang, Donghuang; Cai, Dan; Zhong, Yu; Jiang, Zhao; Zhang, Shengzhao; Xia, Xinhui; Wang, Xiuli; Tu, Jinagping (Frontiers in Chemistry, 2021)
Developing high-quality solid state electrolytes is important for next generation safe and stable solid-state lithium-ion batteries. Herein, a three-dimensional highly porous polymer electrolyte based on poly(vinylidenefluoride-hexafluoropropylene) (PVDF-HFP) with Li6.4La3Zr1.4Ta0.6O12 (LLZTO) nanoparticles fillers (PVDF-HFP-LLZTO) is prepared by electrospinning technique. The PVDF-HFP-LLZTO gel polymer electrolyte possess a high ionic conductivity of 9.44×10-4 S·cm-1 and a Li-ion transference number of 0.66, which can be ascribed to that the 3D hierarchical nanostructure with abundant porosity promotes the liquid electrolyte uptake and wetting and LLZTO nanoparticles fillers decrease the crystallinity of PVDF-HFP. Thus, the solid-state lithium battery with LiFePO4 cathode, PVDF-HFP-LLZTO electrolyte and Li metal anode exhibits enhanced electrochemical performance with improved cycling stability.